IMPLEMENTASI MBKM DALAM MENGHADAPI ERA DISRUPSI &SOCIETY 5.0 DI MAS KMI PADANG PANJANG - Febriyani, Irma; Sabarudin (Universitas Tidar, 2023)
This article discusses about the implementation of the independent learning curriculum (MBKM) in facing disruption era and society 5.0 at MAS KMI Padang Panjang. The industrial revolution 4.0 caused changes in every single live quickly. The existension of humans is replaced by technology. Society 5.0 is coming as an answer to these challenges. Society 5.0 means that the concept of a human based on technology. Indonesia also tries to create superior human who are ready to go to international scale. MBKM was born as the government's effort to create human beings with superior quality and ready to balance the developments. This research is a field research with a qualitative descriptive approach. Data collection techniques were carried out by observation and interviews. The data collection instruments are observation guidelines and interview guidelines. Data analysis techniques use data reduction, data presentation and data verification. As for testing the validity of the data is using data triangulation techniques. The results of the study describe how the implementation of independent learning in MAS KMI Diniyyah Puteri Padang Panjang. MAS KMI Padang Panjang applied individual project-based learning, integration projects and independent curriculum projects, a form of assessment that is not only focus on kognitive aspects but also in affective, aesthetic, physical and social which is contained in 29 indicators of the Quba curriculum, called domain circle, the majoring system is carried out in class XI, a mini thesis munaqasyah session in 3 languages by class XII students, as well as an increase in student HOTS.Keywords: MBKM, Disruption, Society 5.0, MAS KMI Padang Panjang